2000
DOI: 10.1002/1097-0215(20000801)87:3<452::aid-ijc22>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of head and neck cancer in association with GSTT1 nullizygosity for individuals with low exposure to tobacco

Abstract: Increased risk of head and neck cancer in association with GSTT1 nullizygosity for individuals with low exposure to tobacco Tobacco and alcohol are important contributing factors to the development of squamous cell carcinoma of the head and neck (SCCHN) (Blot et al., 1988;Vokes et al., 1993). However, recent case-control studies indicate that SCCHN is also associated with a family history of this cancer (Copper et al., 1995;Foulkes et al., 1995Foulkes et al., , 1996. In addition, second primary tumors, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…The association was more significant in participants with low pack-years. A possible explanation for this interaction could be that genetic susceptibility is most readily identifiable in those with low exposure to the causative environmental factors (Cheng et al 1999;Hamel et al 2000;Zhou et al 2001Zhou et al , 2002, as we have shown previously in the same participants for function-altering polymorphisms in glutathione S-transferase genes (He et al 2004b).…”
Section: Discussionsupporting
confidence: 50%
“…The association was more significant in participants with low pack-years. A possible explanation for this interaction could be that genetic susceptibility is most readily identifiable in those with low exposure to the causative environmental factors (Cheng et al 1999;Hamel et al 2000;Zhou et al 2001Zhou et al , 2002, as we have shown previously in the same participants for function-altering polymorphisms in glutathione S-transferase genes (He et al 2004b).…”
Section: Discussionsupporting
confidence: 50%
“…Our study showed similar frequencies for these genotypes (24.4 and 17.8% for GSTT1 [-] in patients and controls, and 44.4 and 48.9% for GSTM1 [-] in patients and controls). Higher GSTT1 [-] and GSTM1 [-] polymorphism frequencies were observed by Drummond et al 21,22 in Brazilian smokers with oral cavity squamous cell carcinoma (81.8% for GSTT1 [-] and 70.5% for GSTM1 [-] 15,20,22,44 which was not seen in other studies. 5,16,37,39,41,43,46 The combination of these higher risk and null genotypes has also been observed in this type of carcinoma.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, increased risks for disease in carriers of the variant alleles of the CYP1A1 A4889G [22,24] and T6235CC [22,[25][26][27][28] and the GSTM1 [8,23,25,26,[28][29][30][31][32] and GSTT1 null [26,33] genotypes were also previously reported. The divergent results obtained in our study and two previous Brazilian studies [25,30] could be attributed to the different composition of HNSCC subtypes and selection of controls.…”
Section: Discussionmentioning
confidence: 86%